Pengaruh Steel Slag Sebagai Bahan Substitusi Pasir Pada Sebagian Sifat Beton Segar Dan Beton Keras - Eral Lidansyah; Alex kurniawandy; Ermiyanti Ermiyanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The objective of this research is to find the properties of hard and fresh concrete when using steel slag as sand substitution material on concrete with 25 Mpa f’c strength. The research conducted involves the study for workability, chemical resistance, split tension strength and flexural tension strength. The percentage of steel slag used are 0% and 30% of the sand weight. The results of the research show that the 30% slag tend to increase the water required on concrete. Upon the chemical resistance test for, the compression strength increase at 0.37% for concrete aged 7 days and 0.26% for concrete aged 28 days compared to normal concrete. On the split tension strength test for 30% slag substitution the increase on the strength is at 0.44% for concrete aged 7 days and 0.48% for concrete aged 28 days compared to normal concrete. As for flexural strength test, the strength for 30 % slag substitution increase at 0.29% for concrete aged 7 days and 0.11% for concrete aged 28 days compared to normal concrete.Keywords : steel slag, workability, split tension strength, flexural tension strength, chemical resistance.